Koneksitas Linier Musik Terhadap Pertunjukan Tari Tradisi - Maryono Maryono (Greget, 2012)
The linear interconnection of traditional music toward tradition dance performance has important role as accompanied music with vital contribution. Traditional music called karawitanÂ in a dance performance not only has function as accompanied music but also being: (1) guidance for content or meaning; (2) integrated (nyawiji); (3) rested (nglambari); and (4) wrapped (mungkus) in a whole dance and therefore represented a quality art performance. The interconnection of traditionalÂ music toward tradition dance performance was a fusion feel that integrated in expression quality. Keywords : interconnection, traditional music called karawitan, and tradition dance performance.Â